Education through research and learning of school geography - Stumm, Douglas Vinícius (Revista Ensino de Geografia (Recife), 2019)
The students' school learning leaves much to be desired. The data obtained by the external evaluations prove this situation. This problem has multifactorial causes, but the main one is the instructional didactic-methodological model based solely on the classes, which have a pre-established rite and are usually followed strictly by the teachers. All school subjects are affected by this low learning, including the discipline of geography that has not fulfilled its functions in schooling, as well as has becomeinnocuous and unsound due to the way it is worked. In this way, through a bibliographical survey, we seek to expose a more adequate way of working with this knowledge, especially in the construction of the reconstruction of skills and competences, which are necessary today in the globalized world. From this, it is argued that the research education model proposed by teacherPedro Demo would be the most adequate, that is, it fulfills the role of providing significant learning opportunities to the students, granting the teacher the role of mediator of this process. In addition, such didactic-methodological model has as central axis the learning to learn and not the detailed work with a great load of contents, which is quite adequate